2014
DOI: 10.1007/s12053-014-9311-5
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the household energy rebound effect from a practice perspective: spatial and temporal dimensions

Abstract: This article presents and discusses results from an empirical study of people's uses of various types of heat pumps in Norwegian homes. We analyze the rebound effect from a practice theory perspective. In-depth interviews were conducted with 28 homes in 2012 and 2013, and in two cases, we observed the process and aftermath of the installations of heat pumps. We disentangle the motives behind people's acquisition of heat pumps and examine how heat pumps are taken in use, that is, the ways heat pumps form part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…5 Our study builds on two coordinated studies; one economic and one anthropological. 10,6 As in Gram-Hanssen, the qualitative study is framed in a social practice theory perspective to generate insights on how heating practices have changed after heat pumps are installed, and on the reasons behind the observed changes in practices. 5 However, in our paper, the quantitative approach is based on statistical economic modelling (econometrics) of household behaviour, which enables us to identify and quantify different behavioural causes of the observed rebound effects.…”
Section: Introductionmentioning
confidence: 99%
“…5 Our study builds on two coordinated studies; one economic and one anthropological. 10,6 As in Gram-Hanssen, the qualitative study is framed in a social practice theory perspective to generate insights on how heating practices have changed after heat pumps are installed, and on the reasons behind the observed changes in practices. 5 However, in our paper, the quantitative approach is based on statistical economic modelling (econometrics) of household behaviour, which enables us to identify and quantify different behavioural causes of the observed rebound effects.…”
Section: Introductionmentioning
confidence: 99%
“…A German evaluation study on the adoption of energy‐efficient lighting (Schleich, Mills, & Dutschke, ) found that households altered their behavior in response to the lower costs associated with lighting services of energy‐efficient light bulbs, by letting bulbs burn for longer periods of time, or by increasing the luminosity of bulbs. Recent reviews of the literature on rebound effects (Dutschke, Peters, & Schleich, ; Sorrell, Dimitropoulos, & Sommerville, ) indicate that while there appears to be evidence of the occurrence of rebound effects, there is still much debate about the ways in which rebound effects are manifested in the home and “what people actually do when they rebound” (Winther & Wilhite, , p. 596). There are competing explanations, not driven by economics or price signals that may explain why researchers observe an increase in energy use.…”
Section: Technology Changementioning
confidence: 99%
“…Meanwhile, a defense system can be installed, to prevent the system from being interfered with by external factors when processing information and offer a safety guarantee to system information, using firewall and safety protection software, etc. in network technology [5] Fig. 1 shows safety protection between intranet and extranet.…”
Section: Analysis Of the Practice Of Network Technology In Electronicmentioning
confidence: 99%